Banded Iron Travertines at the Ilia Hot Spring (Greece): An interplay of biotic and abiotic factors leading to a modern Banded Iron Formation analogue?. (2nd January 2019) - Kanellopoulos, Christos; Thomas, Camille; Xirokostas, Nikolaos; Ariztegui, Daniel
Abstract: A hot spring at Ilia in the Greek Island of Euboea precipitates iron‐rich travertine at an ore‐grade concentration (up to 35.3 wt% Fe). This hydrothermal chemical sediment system deposits bands of iron oxyhydroxides (ferrihydrite), millimetres to centimetres thick, alternating with calcium carbonate‐dominated layers, creating "Banded Iron Travertine" (BIT). The ferrihydrite laminae display a dendritic texture formed of spherical nodules often covering filaments identified as bacterial stalks of Zetaproteobacteria. These microaerophilic iron‐oxidizing bacteria were identified by their 16S rRNA gene sequences in ferrihydrite‐enriched samples from areas under high water flow. They were missing in the aragonite/calcite‐dominated samples exhibiting features of aerial exposure and cyanobacteria instead. These characteristics, and the relative depletion in Fe‐rich layers of redox‐sensitive elements like Mn and Ce, as well as the presence of halite in Ca‐rich layers, suggest that the bands form by successive changes in hydrothermal flow. This allowed microaerophilic iron oxidation to form Fe‐rich layers, while Ca‐rich bands precipitated when the hydrothermal water had time to equilibrate with the atmosphere. This sea water‐dominated hydrothermal system is enriched in reduced iron and rapidly precipitating carbonates and ferrihydrite in the form of bands, having similarities to "Banded Iron Formation" (BIF). BIF represents archives of Earth's primitive biogeochemistry although the combined abiotic and biotic processes that have likely led to their formation are not fully resolved. Diagenesis and metamorphism have a strong imprint on BIF. Thus, continuous efforts are pursued to identify modern analogues that could help unravel their formation. Although carbonate is not a common feature of BIFs, Ilia system provides an interesting analogue for their depositional processes and potential microbial–mineral associations they may have hosted. It also presents pre‐diagenesis facies association and mineralogy that could bring new clues for unravelling BIF modes of formation and the salient biogeochemical conditions characteristic of their original depositional environment. Abstract : "Banded iron formations" (BIFs) represent archives of the Earth's primitive biogeochemical conditions. The complex associations of abiotic and biotic processes that have likely led to their formation are not fully resolved yet. Here, we present a hydrothermal system from the Greek Island of Euboea, which precipitates iron‐rich travertine at an ore‐grade concentration (up to 35.3 wt% Fe). These chemical sediments consist of micrometric to centimetric bands of iron oxyhydroxides (ferrihydrite) alternating with calcium carbonate (aragonite)‐dominated layers similar to BIFs.